Heterogeneous Economic Integration Agreement Effects - Scott L. Baier; Jeffrey H. Bergstrand; Matthew W. Clance (Center for Economic Studies and ifo Institute (CESifo), 2015)
Gravity equations have been used for more than 50 years to estimate ex post the partial effects of trade costs on international trade flows, and the well-known - and traditionally presumed exogenous – “trade-cost elasticity” plays a central role in computing general equilibrium trade-flow and welfare effects of trade-cost changes. This paper addresses theoretically and empirically the influence of variable and fixed export costs in explaining the likely heterogeneity in the trade-cost elasticity. We offer four potential contributions. First, for motivation, we show empirically that the heterogeneity in various economic integration agreements' (EIAs') partial effects on trade flows far exceeds that explained simply by variation in depth of the trade liberalization. Second, we use standard Armington- and Melitz-type general equilibrium trade models to motivate theoretically the roles of variable trade costs and of fixed and variable export costs, respectively, for explaining (endogenous) heterogeneous partial effects of changes in ad valorem tariff rates on trade flows, as well as on intensive and extensive product margins (with or without network effects and with an untruncated Pareto distribution in the Melitz model). Third, we show empirically that the heterogeneity in EIAs' partial effects on the intensive margin is explained well just by distance and adjacency, capturing variable natural trade costs; however, the heterogeneity in EIAs' partial effects on the extensive margin is explained empirically by distance and adjacency, as well as several other cultural and institutional variables, capturing variable and fixed export costs. Fourth, we show that such estimated heterogeneous effects can predict 83-94 percent of economic welfare effects of EIAs and can potentially predict ex ante a potential EIA's partial trade-flow effect and general equilibrium welfare effect.
Keywords: F10; F12; F13; F14; F15; 330; international trade; economic integration agreements; gravity equation